The effect of 8 weeks exercise activity and estrogen supplementation on proliferation satellite cell in rats - محسن ثالثی; هما شیخانی شاهین; بیتا گرامی زاده; نادر تنیده (Shahid Beheshti University, 2010)
Introduction: Animal and human studies indicated that overtension and stress, releasing the inflammationsubstance and growth factor being produced following exercise lead to satellite cell activation and proliferation.The aim of the present study was to investigate the effect of eight weeks of exercise activity and estrogensupplementation on the proliferation of satellite cells in rats. Methods: Thirty-eight rats were selected andrandomly divided into 4 groups as follows: 1- exercise activity (E), 2- Estrogen supplementation (ES), 3-exercise activity + Estrogen supplementation (EE), 4- control. Then, E and EE groups performed enduranceexercise for 8 weeks, 3 sessions in each. In each week, ES and EE groups were implanted subcutaneously with0.6 of Estrogen supplement. Soleus muscle was retracted and placed into 10% of Formalin. In a pathologicallab, satellite cell numbers were counted and recorded using a light microscope through Hemotoxin Eosinstaining and Immunohistochemistry for CD 56. Results: The results of one-way ANOVA indicated that theproliferation of satellite cells were differents on study groups. Exercise activity causes a 16% increase insatellite cell number in rats, while a 71% decrease in satellite cell number was observed in long-term exerciseactivity plus estrogen supplementation group. Besides the research result indicated a 5 time -increase insatellite cells in group received estrogen supplementation for long term. Conclusion: estrogen may act ininflammation responses and skeletal muscle injuries as a consequence of unaccustomed exercise or otherdetrimental effects. Moreover, this research confirmed that estrogen supplementation effects on satellite cellproliferation in rats that it would appear that many different factors play a role in increase and proliferation ofthese cells, so it has been influenced by estrogen levels.